Pengaruh Jenis Kontrasepsi Suntik dengan Kenaikan Berat Badan pada Akseptor KB di PMB Wahyuning Purwati Kabupaten Sleman - Deski Latifah; Fayakun Nur Rohmah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Injection contraception is one of the most widely used family planning methods in Indonesia. However, its use is often associated with side effects in the form of weight gain. The commonly used types of injection contraception are the 1-month and 3-month injections, each containing different hormonal contents, which are suspected to have different effects on the weight of the acceptors. The aim of this study is to determine the effect of 1-month and 3-month injection contraception on weight gain in family planning acceptors at PMB Wahyuning Purwati Sleman Regency. This research employs a quantitative method with a cross-sectional approach. A sample of 37 injectable contraceptive acceptors was selected using accidental sampling technique. The instrument used was a questionnaire. Data analysis was performed using paired sample t-test and independent t-test to determine body weight changes before and after using injectable contraceptives. The results showed an increase in body weight among users of the 1-month injectable contraceptive with an average of 3.158 kg (p<0.000) and among users of the 3-month injectable contraceptive with an average of 3.653 kg (p<0.006). Both types of injectable contraception showed a significant effect on weight gain. The weight gain was greater in users of the 3-month injection compared to the 1-month injection. There is a need for more intensive education and counseling for contraceptive acceptors regarding the side effects of injectable contraception and the importance of maintaining a healthy lifestyle.